PELATIHAN PENGGUNAAN APD PADA PEKERJA PROYEK PEMBANGUNAN - Rizka Annisa; Herlina J. El-Matury (INSTITUT KESEHATAN DELI HUSADA, 2021)
Construction projects are inherently dangerous and can lead to accidents. Therefore, this research was conducted to determine the potential hazards of K3 in the work process of building and building components, with an emphasis on mechanical hazards, chemical hazards, physical hazards and electrical hazards. This study uses an observational method to describe, the aim is to determine the potential hazards of K3 from the process of working on structural parts and the process of working on parts of the building. This research was conducted on the construction project of the Agung Lubk Pakam Hospital. The results showed that the greatest K3 hazard potential was found in structural work, namely in the casting process, such as falling from a concrete barrel, being hit by a concrete barrel, exposed to steel slings, exposed to iron. sheets, etc. The concrete dough that falls off the scaffold is exposed to dust, vibration, heat and noise. In construction work, the biggest K3 hazard potential is in roof work, where workers are exposed to formwork and iron rings, their feet and hands are clamped by formwork and iron rings, and workers' hands are scraped off by iron and iron rings on log formwork. , respiratory problems, skin and eye irritation due to waterproof coating, exposure to dust, vibration, heat and noise. It is very important to consult with workers about the use of PPE, the project must also make a K3 mark in every dangerous work area and give sanctions to those who do not use PPE.